Reliability and validity of sit-to-stand test protocols in patients with coronary artery disease - Wang, Zheng; Yan, Jianhua; Meng, Shu; Li, Jiajia; Yu, Yi; Zhang, Tingting; Tsang, Raymond C. C.; El-Ansary, Doa; Han, Jia; Jones, Alice Y. M. (Frontiers in Cardiovascular Medicine, 2022)
Background: Sit-To-Stand (STS) tests are reported as feasible alternatives for the assessment of functional fitness but the reliability of these tests in people with coronary artery disease (CAD) has not been reported. This study explored the test-retest reliability, convergent and known-groups validity of the five times, 30-second and 1-minute sit-to-stand test (FTSTS test, 30-s STS test and 1-min STS test respectively) in patients with CAD. The feasibility of applying these tests to distinguish the level of risk for cardiovascular events in CAD patients was also investigated. Methods: Patients with stable CAD performed a 6MWT and 3 STS tests in random order on the same day. Receiver operating characteristic (ROC) curve analyses were conducted using STS test data to differentiate patients with low or high risk of cardiovascular events; risk level was determined by distance covered in the 6MWT as > or ≤419m. Thirty patients repeated the 3 STS tests on the following day. Results: 112 subjects with diagnoses of atherosclerosis, post-percutaneous coronary intervention, or post-acute myocardial infarction participated in the validity analysis. All 3 STS tests demonstrated moderate but significant correlation with the 6MWT (coefficient values r for the FTSTS, 30-s STS and 1-min STS were -0.53, 0.57 and 0.55 respectively). Correlation between left ventricular ejection fraction (LVEF) and all STS tests and between 6MWT and LVEF was only weak (r values ranged from 0.27 to 0.31). Subgroup analysis showed participants in the atherosclerosis group performed best in all tests. The areas under the curve (AUC) was 0.80 for FTSTS (sensitivity: 75.0%, specificity: 73.8%, optimal cut-off: >11.7 seconds), and the AUC, sensitivity, specificity and optimal cut-off for 30-s STS and 1-min STS test was 0.83, 75.0%, 76.2%, ≤12 times and 0.80, 71.4%, 73.8%, ≤23 times) respectively. The interclass correlation coefficient (ICC) scores for repeated measure of the 3 tests were 0.96, 0.95 and 0.96 and computed minimal detectable change (MDC95) was 1.1 seconds, 1.8 times and 3.9 times. Conclusions: All STS tests demonstrated good test-retest reliability, convergent and known-groups validity. STS tests may discriminate low from high levels of risk for a cardiovascular event in patients with CAD.